2018
DOI: 10.1016/j.cell.2018.10.028
|View full text |Cite
|
Sign up to set email alerts
|

NKG2A Blockade Potentiates CD8 T Cell Immunity Induced by Cancer Vaccines

Abstract: Summary Tumor-infiltrating CD8 T cells were found to frequently express the inhibitory receptor NKG2A, particularly in immune-reactive environments and after therapeutic cancer vaccination. High dimensional cluster analysis demonstrated that NKG2A marks a unique immune effector subset preferentially co-expressing the tissue-resident CD103 molecule, but not immune checkpoint inhibitors. To examine if NKG2A represented an adaptive resistance mechanism to cancer vaccination, we blocked the receptor with an antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
231
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(272 citation statements)
references
References 59 publications
16
231
1
Order By: Relevance
“…In mice, loss of function of Qa-1b (equivalent to HLA-E in humans) resulting from in vivo CRISPR screening increased sensitivity of tumor cells to immune cells (80). Correlative studies in ovarian and cervical carcinomas have shown a predominant infiltration of CD8 + lymphocytes expressing NKG2A (26,81), and recently published studies indicate that an anti-NKG2A antibody can augment T cell antitumor activity (41,82). Thus, the approach described here could potentially be extended to protocols of adoptive T cell therapy of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, loss of function of Qa-1b (equivalent to HLA-E in humans) resulting from in vivo CRISPR screening increased sensitivity of tumor cells to immune cells (80). Correlative studies in ovarian and cervical carcinomas have shown a predominant infiltration of CD8 + lymphocytes expressing NKG2A (26,81), and recently published studies indicate that an anti-NKG2A antibody can augment T cell antitumor activity (41,82). Thus, the approach described here could potentially be extended to protocols of adoptive T cell therapy of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This program (ICA 25) was driven by Klrc1/NKG2A and Lag3 (Figure 3G-H), and its expression was uncoupled from that of other inhibitory receptors such as PD-1, TIM-3 or CTLA4, suggesting a potential benefit of targeting these two programs simultaneously. Indeed, dual blockade of PD-1 and LAG-3 results in robust and synergistic reinvigoration of Tex cells in cancer 52 and chronic infection 53 , while NKG2A blockade has been recently shown to potentiate CD8 T cell immunity induced by cancer vaccines 54 .…”
Section: Discussionmentioning
confidence: 99%
“…NKG2A blockade in animal model of HCV infection led to enhanced NK and CD8+ Tcell functions promoting HCV clearance [124]. NKG2A blockade combined with anti-PD-1/PD-L1 blockade was recently shown to enhance NK and T-cell anti-tumour response [125,126] in murine lymphoma tumour models and in human in vitro experiments [125]. Preliminary results of a phase II trial combining monalizumab, a humanised anti-NKG2A antibody, and cetuximab, an anti-EGFR in head and neck squamous cell carcinoma patients showed a 31% objective response rate (NCT02643550).…”
Section: Nk Cell-based Therapiesmentioning
confidence: 99%